Thermo-electromagnetic modeling of coated superconductor coils with metal insulation. (8th October 2021) - Wang, Ruichen; Ma, Guangtong; Zhou, Pengbo; Gong, Tianyong; Li, Songlin
Abstract: The use of metallic sheets as the insulator in a coated superconductor coil is able to increase its turn-to-turn contact resistance for shortening the charging/discharging delay while preserving the self-protection ability. To theoretically understand and predict the properties of the metal-insulation coils, we developed a thermo-electromagnetic model, in which a modified equivalent circuit for electrically representing the metal-insulation coils is built to take the effect of insulator into account. The effectiveness and versatility of this model are verified by different experimental scenarios, e.g., charging, sudden-discharging, and overcurrent. Enabled by the validated model, we carried out a set of case studies and observed that, (a) the metal-insulation coil with a low resistivity and high thermal conductivity metallic insulator is preferable to achieve a better thermal stability; (b) there exists an optimal insulator thickness for realizing the shortest charging delay, but a thicker insulator is superior for realizing a stronger thermal stability; (c) contact resistivity of over 10 4 μΩ· cm 2 can weaken the current sharing in the radial direction, which would deteriorate the thermal stability of the metal-insulation coils, although it can significantly suppress the charging delay, implying that a tradeoff is always needed to balance the charging delay and thermal stability when determining the contact resistivity. These findings, mostly being inaccessible from the experiments, provide guidance toward practical applications of metal-insulated coated superconductor coils.